Data on prevalence of hypertension and blood pressure in Turkey: Systematic review, meta-analysis and meta-regression of epidemiological studies on cardiovascular risk factors - Mustafa Kılıçkap; Cem Barçın; Hüseyin Göksülük; Doruk Karaaslan; Necla Özer; Meral Kayıkçıoğlu; Dilek Ural; Mehmet Birhan Yılmaz; Adnan Abacı; Mustafa Arıcı; Bülent Altun; Lale Tokgözoğlu; et al. (KARE Publishing, 2018)
Objective: Cardiovascular risc factors may show significant changes over the years. A systematic review and meta-analysis of epidemiological studies conducted in Turkey was performed to assess the latest profile and temporal changes in cardiovascular risk factors. Presented here are the data on hypertension (HT) and blood pressure (BP). Methods: Ovid Medline, the Web of Science Core Collection, and the Turkish Academic Network and Information Center (ULAKBIM) were searched for epidemiological studies conducted in Turkey during the last 15 years. In addition, the web pages of the Ministry of Health, the Turkish Statistical Institute, and associations of cardiology, nephrology, and endocrinology were searched for appropriate studies. Regional studies were excluded. The studies included were assessed with a bias score developed by our team, then categorized as having a low risk or a high risk of bias. The crude values of HT prevalence and BP were pooled using a random effects model. Meta-regression was performed to explain heterogeneity and to assess temporal changes. Results: The agreement between the 2 authors on the selection and bias scoring of the studies was perfect (Kappa ≥0.95). There were 7 (n=73218) studies providing HT prevalence data, and 8 (n=75879) studies with BP data. The heterogeneity between the studies was high. Meta-analysis of the studies with a low risk of bias indicated that the crude prevalence of HT is higher in women, but that BP levels were similar in both sexes. The HT prevalence and BP value decreased between 2003 and 2012; however, the number of hypertensives stabilized at approximately 15 million, and the number of uncontrolled hypertensives, despite some decrease, was around 11 million. Conclusion: Despite some improvement, HT is still an important public health problem in Turkey.